2022
DOI: 10.1152/ajpheart.00050.2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraventricular septal fiber orientation on cardiac electromechanical function

Abstract: Cardiac fiber direction is an important factor determining the propagation of electrical activity, as well as the development of mechanical force. In this paper, we imaged the ventricles of several species with special attention to the intraventricular septum to determine the functional consequences of septal fiber organization. First, we identify a dual-layer organization of the fiber orientation in the intraventricular septum of ex-vivo sheep hearts using diffusion tensor imaging at high field MRI. To expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The presence of abrupt change of fiber orientation may be associated with a conduction block or ectopic beat in pathological hearts. Combination of submillimeter diffusion weighted acquisition with dedicated high-level image processing could increase our knowledge of cardiac microstructure and help to understand cardiac electrophysiology by differentiating normal to remodeled or pathologic discontinuities [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of abrupt change of fiber orientation may be associated with a conduction block or ectopic beat in pathological hearts. Combination of submillimeter diffusion weighted acquisition with dedicated high-level image processing could increase our knowledge of cardiac microstructure and help to understand cardiac electrophysiology by differentiating normal to remodeled or pathologic discontinuities [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional active contraction in cross-fiber directions was needed for the sectorwise and a global rule-based representation, to achieve physiological behaviour. In an ex-vivo analysis of the myocardial tissue, Rodríguez-Padilla et al (2022) found a bilayer structure in the septum, with two different primary directions of fiber orientation and showed the influence of this local feature on the stress distribution. These sensitivity studies suggest that patient-specific, locally heterogeneous microstructure is important for patient-specific modelling.…”
Section: Introductionmentioning
confidence: 98%
“…The sensitivity of simulation results (such as torsion, stress, and strain distributions) to microstructure has been investigated in previous studies, revealing an essential influence of fiber orientation suggesting the need for individualized microstructure in patient-specific simulations ( Geerts et al, 2003 ; Wang et al, 2013 ; Palit et al, 2015 ; Nikou et al, 2016b ; Pluijmert et al, 2017 ; Gil et al, 2019 ; Campos et al, 2020 ; Guan et al, 2020 ; Barbarotta et al, 2021 ; Rodríguez-Padilla et al, 2022 ). Sensitivity studies using a rule-based fiber orientation with varying helix and transverse angles have revealed changes in the distribution of myofiber stress and shortening of up to 9 percentage points resulting from a difference in fiber direction of 8° ( Geerts et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…All hearts were fixed with a solution containing formalin (10%) and a gadolinium-based contrast agent (Dotarem, Guerbet, Paris, France) at 0.2% of total volume of perfusion, by retrograde perfusion from the aorta. Sample preparation was performed as previously described [ 16 , 18 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Experimental characterization of the microstructure organization is also largely used in realistic or patient-specific models for biomechanical, or electrophysiological models. Recently, Doste et al [ 17 ] underlined the discrepancy between cardiomyocyte orientation distributions computed by rule-based models with histological or MRI data in the IVS due to the dual-layer organization [ 18 ], and in the RVIP. Thus, to expand the scope of the result, based on the observed human experimental data, we model the effects of cardiomyocyte orientation on cardiac electrophysiology (EP), computing local activation times and pseudo-ECGs.…”
Section: Introductionmentioning
confidence: 99%